S3-Leitlinie „Prophylaxe, Diagnostik und Therapie der Hepatitis-C-Virus (HCV) -Infektion“ = Prophylaxis, diagnosis and therapy of hepatitis-C-virus (HCV) infection : the German guidelines on the management of HCV infection - Sarrazin, Christoph; Schirmacher, Peter (Zeitschrift für Gastroenterologie, 2018)
Thieme E-Books & E-Journals